International and national perspective of disability and policy disconnect in Pakistan: a narrative review - Mumtaz, Nazia; Saqulain, Ghulam (Journal of the Pakistan Medical Association, 2022)
In the developed societies, supportive environmental, physical and social conditions enable participation of persons with disabilities in the mainstream through actions, like provision of ramps and reserved parking. In contrast, in the developing countries like Pakistan, with focus on visual disability, years lost to disabilities compromise and restrict the productive life span of the disabled. The current narrative review was planned to highlight the perspective of disability in the context of Pakistan to bring to limelight the issues requiring immediate focus of the health authorities and the government through a holistic and sustainable approach. Of the 177 publications found on literature search, 33(%) English-language, full-text studies were reviewed. To address disability issues, long-term sustainable actions, like health reforms, including ensuring availability of rehabilitation professionals in hospitals, legislative reforms to initiate relevant legislations, capacity-building of persons with disabilities, including their mainstreaming, are deemed essential.